Rancang Bangun Sistem Informasi Sistem Penjualan Hand Tools Berbasis Web pada PT. XYZ Kota Bekasi - Dyan Yuliana (Jurnal Penelitian Rumpun Ilmu Teknik, 2025)
This research is entitled "Design and Development of a WEB-Based Hand Tools Sales Information System at PT. XYZ Bekasi City”. The purpose of this research is to find out what the Hand Tools sales information system is like, and the obstacles or constraints faced in the information system, as well as providing solutions to problems with the Hand Tools sales system. Where is the sales process for Hand Tools used at PT. XYZ in Bekasi currently still uses conventional methods, namely by recording in bookkeeping and assisted by Microsoft Office Excel, so that the sales process is not effective and efficient. Very often, making invoices, travel documents, recording goods data, collecting customer data and recording transactions is very inaccurate. From these problems, the idea emerged to create a web-based information system, in which computerized sales management could be carried out. The research methods used are Library Research and Field Research.